Muslim Divorced Women’s Right to ‘Mata’a’: A Sri Lankan Perspective - Ziyana, N. (My University, 2012)
In the event of the dissolution of marriage, the maintenance of a Muslim divorced woman by the husband is a contentious issue in Sri Lanka and other countries1. Although Muslim Law in most countries, including Sri Lanka, recognizes that a divorced wife should be maintained by her husband till the end of idda (waiting) period or if such a woman is pregnant, until she delivers the baby, and till the end of the nursing period of the offspring, this obligation does not extend beyond this stage. Thus, a divorced Muslim woman is worse off than her non Muslim counterpart who is entitled to alimony.2 This issue should be considered carefully in the context of Muslim marriage, because a Muslim wife is under an obligation of obedience to the husband, which makes most wives dependants on their husbands.3 Not only that, this position also leaves divorced Muslim women in a vulnerable position in the community and challenges the sustainability of Sri Lankan Society.